Editorial (Revista Lusófona de Economia e Gestão das Organizações, 2019)
EditorialThe Lusophone Journal of Economics and Organizational Management (R-LEGO) is an editorial project of the Department of Economics and Management of the Economics and Management School [ECEO], connected to the Research Centre of the Department (CEO - Economics and Organizational Research Centre) and CIPES (Research Centre of Politics, Economy and Society).It is aimed to accept students, teachers, researchers and professionals who share interests and scientific concerns.The ECEO has been consolidating its position both as a trainer and research hub. In this sense we felt the need to have a publication that would reflect all research that has been conducted in recent years.Several students selected their undergraduate and master's degrees in ECEO, where they had the opportunity not only to deepen their knowledge but also to share experiences with well-known professionals in the market/business work.Their work and dissertations have been integrated in research projects being supervised by teachers with the best qualifications in each case. All teachers, as instructors, are encouraged to conduct original scientific studies that may contribute to increase scientific and academic discussion.This way, the ECEO recovered a journal that was once created as a way to be an open space to society and researchers in order to disseminate the results of their studies, reflections and researches. It is intended to offer a scientific reflection space ensuring accuracy and exemption of thought and ideas, defending the Lusophony as a distinctive part of this project.Therefore, R-LEGO integrates various analysis and training perspectives as a result of its formative offer at ECEO. At a bachelor level we have several courses ranging from ranging from Accounting, Taxation and Auditing, Economics, Business Management, Human Resources Management, Safety and Hygiene at Work and finally Tourism. At a Master level, we can highlight the Masters in Accounting and Taxation, Economics, Business Management and Tourism.We have created an Editorial Board and a Scientific Commission that integrates renowned academics and professionals from various scientific national and international areas in order to assure a critical analysis of the appropriateness and reasonableness of the proposed articles.We are still concluding international protocols that may allow us to strengthen the scope of this journal.We are aware of the challenge that we are assuming and we believe that the rigor, impartiality and quality will be maintained through the commitment of the whole team that has embraced this project. Editorial BoardAna BrasãoAntónio CostaEduardo Moraes SarmentoMaria Isabel Duarte Scientific CommissionAdelino Torres (Portugal)Alcides de Moura (Spain)Alla Kravets (Russia)Amanda Barrie (United Kingdom)Carlos Aik (Mozambique)Cristina Pego (Portugal)Dean Patton (United Kingdom)Fausto Santos (Angola)Fernando Vunge (Angola)Gualberto do Rosário (Cape Verde)Jon Weaver (United Kingdom)Licínio Cunha (Portugal)Lisbeth Jensen (Denmark)Marcos Caiado (Brazil)Mário Ceitil (Portugal)Michael Koniordos (Greece)Nuno Almeida (Portugal)Olga Shabalina (Russia)Paulo Revés (Portugal)Rasmus Sømod (Denmark)Ricardo Pinto (Brazil)Sandra Loureiro (Portugal)Sérgio Ribeiro (Mozambique)Søren Lydig Kristensen (Denmark)Thanh Huynh (United Kingdom)Vitor Brasão (Mozambique)